2021
DOI: 10.3390/ijms22147343
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Responses to Cadmium Exposure in Two Contrasting Durum Wheat Genotypes

Abstract: Cadmium is a heavy metal that can be easily accumulated in durum wheat kernels and enter the human food chain. Two near-isogenic lines (NILs) with contrasting cadmium accumulation in grains, High-Cd or Low-Cd (H-Cd NIL and L-Cd NIL, respectively), were used to understand the Cd accumulation and transport mechanisms in durum wheat roots. Plants were cultivated in hydroponic solution, and cadmium concentrations in roots, shoots and grains were quantified. To evaluate the molecular mechanism activated in the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…On the other side, the gene coding for the SNARE protein resulted down-regulated ( Figure 13 ); however, in the description associated with the annotation of this gene was reported the caption “SNARE associated Golgi protein family” suggesting that the gene codes for a SNARE protein involved in the fusion of vesicles with Golgi membranes; in this perspective, its down-regulation makes sense to favor vesicular transport toward the plasma membrane and exocytosis. Among the up-regulated genes, we also found the genes YSL2, IREG2, HMA5 and HMT1 ( Figure 10 ); the last three are well-known genes coding for transporters involved in Cd detoxification and tolerance in Arabidopsis ( Long et al, 2010 ; Park et al, 2012 ; Wu et al, 2012 ) and in durum wheat ( Sabella et al, 2021 ) while YSL2 codes for a nicotianamine transmembrane transporter ( Conte et al, 2013 ). Taken together, the presented data indicate that, in the cv.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other side, the gene coding for the SNARE protein resulted down-regulated ( Figure 13 ); however, in the description associated with the annotation of this gene was reported the caption “SNARE associated Golgi protein family” suggesting that the gene codes for a SNARE protein involved in the fusion of vesicles with Golgi membranes; in this perspective, its down-regulation makes sense to favor vesicular transport toward the plasma membrane and exocytosis. Among the up-regulated genes, we also found the genes YSL2, IREG2, HMA5 and HMT1 ( Figure 10 ); the last three are well-known genes coding for transporters involved in Cd detoxification and tolerance in Arabidopsis ( Long et al, 2010 ; Park et al, 2012 ; Wu et al, 2012 ) and in durum wheat ( Sabella et al, 2021 ) while YSL2 codes for a nicotianamine transmembrane transporter ( Conte et al, 2013 ). Taken together, the presented data indicate that, in the cv.…”
Section: Discussionmentioning
confidence: 98%
“…The grain surfaces were sterilized, and seeds sprouted in Petri dishes covered with humified vermiculite. After sprouting (about 1 week in the dark and temperature at 8°C), seedlings were transplanted in cylindric pots ( h = 50 cm, Ø = 10 cm) filled with perlite, soaked with deionized water, and quickly moved to the hydroponic system as described by Sabella et al, 2021 . Three seedlings were planted in each pot, and, for each treatment, three tubes were assembled (three biological replicates).…”
Section: Methodsmentioning
confidence: 99%
“…Wheat, in particular, is highly vulnerable to Cd toxicity as it tends to accumulate Cd in the grain [ 61 ], thus affecting human health. As in other plant species, comparative transcriptomic studies on wheat roots revealed a multilevel coordination of Cd uptake, transport, sequestration and detoxification, both in durum [ 39 , 40 ] and bread wheat [ 62 ]. Recently, the transcriptomes of roots from two commercial durum cultivars and from two near isogenic lines with contrasting Cd accumulation in grains were analyzed [ 39 , 40 ], identifying the key genes and mechanisms involved.…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…As in other plant species, comparative transcriptomic studies on wheat roots revealed a multilevel coordination of Cd uptake, transport, sequestration and detoxification, both in durum [ 39 , 40 ] and bread wheat [ 62 ]. Recently, the transcriptomes of roots from two commercial durum cultivars and from two near isogenic lines with contrasting Cd accumulation in grains were analyzed [ 39 , 40 ], identifying the key genes and mechanisms involved. The mRNA sequencing of Creso and Svevo durum cultivars in response to Cd treatment identified about 7100 DEGs in root and shoot tissues, revealing a conserved strategy to detoxify cells from Cd [ 39 ].…”
Section: Abiotic Stressesmentioning
confidence: 99%
See 1 more Smart Citation